The Micmacs of Newfoundland: A Resurgent Culture - Anger, Dorothy C. (Culture, 1981)
Over the past decade, following the loss of their traditional systems of social organization and lack of recognition as a native people, the Micmac Indians of Newfoundland have been engaged in a process of cultural revitalization. Utilizing their history in the re-creation of a cultural identity, an important symbol has been the land and their relationship to it. In this paper, the significance of the land provides a basis for the understanding of this political and cultural resurgence of Indian resurgence.